Dampak Anestesi Umum, Spinal dan Epidural Terhadap Tempat Rawat Pasca Operasi dan Skor Apgar pada Pasien Preeklampsia Berat yang Dilakukan Seksiosesaria di RSUP Dr Sardjito Tahun 2004-2006 - Pramono, Ardi; Uyun, Yusmein; Suryono, Bambang (Universitas Muhammadiyah Yogyakarta, 2008)
The author want to know the place of post operative care and Apgar score of general and regional anesthesia in patients with severe preeclampsia who will be performed sectiosecaria in Sardjito Hospital Yogyakarta year 2004-2006. Data will be collected from medical record. The study will be conducted with cohort retrospective and sample method with consequtive sampling. The inclusion criteria of severe preeclampsia patients were systolic pressure e â€ 160mmHg and or diastolic pressure e